Comparative study of the clinical efficacy of the first domestic bioanalogue of tocilizumab based on the results of a randomized clinical trial of phase III - E. V. Akatova; Yu. S. Bakhareva; O. V. Bugrova; I. B. Vinogradova; E. V. Gerasimova; Yu. E. Drevina; O. B. Ershova; E. V. Zonova; Yu. I. Ivanova; E. P. Ilivanova; M. M. Kostik; D. G. Krechikova; et al. (Современная ревматология, 2024)
The article discusses the results of a comparative phase III clinical trial of the efficacy and safety of the biosimilar Complarate (CPR; JSC Generium, Russia) and the reference drug Actemra (ACT; F. Hoffmann-La Roche Ltd., Switzerland) to assess their equivalence in patients with rheumatoid arthritis, RA (NCT06475508 clinicaltrials.gov).Materials and methods. Male and female patients aged 18–75 years with RA with moderate to high disease activity and insufficient response to methotrexate (MTX) monotherapy and/or poor tolerability of MTX and/or insufficient response or intolerance to other standard DMARDs in combination with or without MTX were enrolled in the study. 464 (89.4%) patients were randomized in a 2:1 ratio into two groups. The study and the reference drug were administered as an intravenous infusion at a dose of 8 mg/kg once every 4 weeks. The primary endpoint was the proportion of patients with an ACR20 after 24 weeks of therapy.Results and discussion. The proportion of responders in CPR group was 91.2%, and in ACT group – 90.7% (p = 0.866). The difference between the groups was 0.5% (95% CI: -5,2%−6,1%), which is fully within the declared boundaries of recognition of therapeutic equivalence. Comparability of the biosimilar CPR and the reference drug ACT is also confirmed by the results of secondary efficacy endpoints: the proportion of patients with ACR50/70, dynamics of the DAS28, SDAI, CDAI, the functional activity of patients (HAQ), laboratory parameters of inflammatory activity (ESR and CRP). Comparability of the study and the reference drugs is also demonstrated by the results of the safety analysis.Conclusion. Based on the results of the clinical study, it has been proven that CPR (JSC Generium, Russia) is a biological analogue of ACT (F. Hoffmann-La Roche Ltd., Switzerland).